THE INFLUENCE OF RECRUITMENT, SELECTION AND WORK PLACEMENT ON EMPLOYEE PERFORMANCE AT PT. INDO PORCELAIN - Iin Hardiyanti; Muhamad Abdul Rosyid; Isrok Isrok (Jurnal Comparative: Ekonomi dan Bisnis, 2021)
Management of human resources (HR) is important in achieving goals because the company expects good performance from each employee in carrying out the tasks that have been given. Therefore, the company realizes that human resources (HR) is the basic capital in the process of achieving the goals that have been set. The research approach that the authors use is descriptive and associative research with a quantitative approach. The method used in this research is to use the survey method, where the author distributes questionnaires for data collection. In the results of research on recruitment (X1) and employee performance (Y), the results obtained were tcount > ttable (6.760 > 1.67866) with a significance of 0.000 <0.05. Then H0 is rejected and Ha is accepted, meaning that Recruitment (X1) has a positive and significant influence on Employee Performance at PT Indo Porcelain, so H1 is thus proven (accepted). In the selection research results (X2) and Employee Performance (Y) obtained tcount > ttable (1.764 > 1.67866) with a significant 0.001 <0.05. Then H0 is rejected and Ha is accepted, meaning that Selection (X2) has a positive and significant influence on Employee Performance, thus H1 is proven (accepted). In the selection research results (X2) and Employee Performance (Y) obtained ttable = 1.67866 so tcount > ttable (4.675 > 1.67866) with a significance of 0.001 <0.05 . Then H0 is rejected and Ha is accepted, meaning Work Placement (X3 ) has a positive and significant effect on employee performance, thus H1 is proven (accepted). The overall research results explain that recruitment selection and job placement have a significant influence on the performance of PT Porcelain employees.